2017
DOI: 10.1007/s40544-017-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical effects on the sliding friction of Ag and Au(111)

Abstract: Abstract:We have investigated the sliding friction behavior of metallic couples with different enthalpy of mixing or reaction by friction force microscopy. Comparing the friction behavior of miscible and immiscible couples we find that in the first case friction is governed by adhesion while the shear strength is low (τ = 3-6 MPa). In the latter case of immiscible couples, adhesion is found to be low and the shear strength is large (τ ≈ 70 MPa). Statistical analysis of atomic stick-slip images recorded on an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
5
12
1
Order By: Relevance
“…The obtained value for the shear strength between Au and HOPG was comparable with the previously reported value for an Au tip sliding on an Au(111) surface, where we found s ¼ 24.21 MPa. 9 The friction force hF f i value averaged over the whole range of normal force values was found to be high for larger adhesion forces F ad , i.e. hF f i Au ¼ 0.62 AE 0.07 nN and F ad,Au ¼ À1.23 AE 0.11 nN and hF f i Pt ¼ 5.73 AE 1.19 nN and F ad,Pt ¼ À9.57 AE 0.21 nN.…”
Section: Resultsmentioning
confidence: 89%
“…The obtained value for the shear strength between Au and HOPG was comparable with the previously reported value for an Au tip sliding on an Au(111) surface, where we found s ¼ 24.21 MPa. 9 The friction force hF f i value averaged over the whole range of normal force values was found to be high for larger adhesion forces F ad , i.e. hF f i Au ¼ 0.62 AE 0.07 nN and F ad,Au ¼ À1.23 AE 0.11 nN and hF f i Pt ¼ 5.73 AE 1.19 nN and F ad,Pt ¼ À9.57 AE 0.21 nN.…”
Section: Resultsmentioning
confidence: 89%
“…[3,4], where almost no frictional energy dissipation was measured. In this load regime also, the authors recently showed how the shear strength of such junctions can be tuned by changing the metallurgical affinity between the contact materials [7]. Also, nanoscale wear experiments by AFM demonstrated the determinant role of plastic deformation mechanisms [8,9].…”
Section: Introductionmentioning
confidence: 94%
“…In Refs. [6,7], friction between Au islands and graphite was studied. AF 2=3 n dependence of the friction force on gold islands measured in ambient conditions was observed, where F n is the normal force [6].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the lubricating effect of graphene is understood as arising from its chemical inertness and large in-plane stiffness [ 15 ]. In contrast to metals where the single nanoscale asperity sliding contact is governed by the formation of adhesive junctions and their shearing, the leading mechanism of wear-less friction of graphene has been identified as puckering [ 16 , 17 , 18 ]. The nanoscale wear protection of graphene grown on Pt (111) has been simulated and experimentally verified in Reference [ 19 ].…”
Section: Introductionmentioning
confidence: 99%